2003
DOI: 10.1074/jbc.m212299200
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Formation and Action of the Ternary Complex Revealed in Living Cells Using a G-protein-gated K+ Channel as a Biosensor

Abstract: Traditionally the consequences of activation of G-protein-coupled receptors (GPCRs) by an agonist are studied using biochemical assays. In this study we use live cells and take advantage of a G-protein-gated inwardly rectifying potassium channel (Kir3.1؉3.2A) that is activated by the direct binding of G␤␥ subunit to the channel complex to report, in real-time, using the patch clamp technique the activity of the "ternary complex" of agonist/receptor/G-protein. This analysis is further facilitated by the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
5
39
0
Order By: Relevance
“…We originally investigated such issues to explain what factors contribute to the rapid activation of GIRK channels by Gi͞o coupled receptors. In addition, we had previously found that the activation rate through a receptor-G protein fusion was identical to that of the normal receptor and increasing G protein concentration did not affect signaling kinetics (12). GPCR G protein precoupling can contribute to fast activation rates and can explain our previous experimental observations.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We originally investigated such issues to explain what factors contribute to the rapid activation of GIRK channels by Gi͞o coupled receptors. In addition, we had previously found that the activation rate through a receptor-G protein fusion was identical to that of the normal receptor and increasing G protein concentration did not affect signaling kinetics (12). GPCR G protein precoupling can contribute to fast activation rates and can explain our previous experimental observations.…”
Section: Discussionsupporting
confidence: 59%
“…Patch clamping was carried out as described (12,30). Cell capacitance was Ϸ15 pF, and series resistance (Ͻ10 M⍀) was at least 75% compensated by using the amplifier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have addressed the role of receptor-Gprotein collision in GIRK activation by fusing GPCRs and G-proteins and by varying the abundance of these proteins to either eliminate or manipulate the frequency of receptor-Gprotein collision. One of these studies concluded that receptor-G-protein collision was rate-limiting (Vorobiov et al, 2000), whereas the other reached the opposite conclusion (Benians et al, 2003). In both of these studies, the GIRK activation rate was limited by the heterologous expression system, and it has since been shown that fusing receptor and G-protein does not eliminate intermolecular collision coupling (Molinari et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the G protein activation steps, signal termination with GTP hydrolysis by the G␣ subunit and G␤␥ reassociation also impacts the kinetics and amplitude of agonist-activated GIRK currents. The ternary complex consisting of agonist, GPCR, and G protein influences the time course of agonist-elicited GIRK channel currents (3), supporting the notion that isoform composition of different GPCR-G␣ i/o ␤␥ protein-RGS protein-GIRK channel signaling complexes have different kinetic properties that affect their functional output (4). We recently reported notable differences in the gating properties of GIRK channels activated by muscarinic m2 receptors coupled specifically to PTX-insensitive G␣ i isoforms (G␣ i1 , G␣ i2 , or G␣ i3 ) versus G␣ o isoforms (G␣ oA or G␣ oB ) in the Xenopus oocyte system (4).…”
mentioning
confidence: 99%